FRAMING ISU POLITIK IDENTITAS ANIES-CAK IMIN DALAM PILPRES 2024 PADA PEMBERITAAN KUMPARAN.COM DAN METROTV - Puji Laksono; Laila Akmalia (Program Studi Pendidikan Soiologi Antropologi, FKIP-UNS, 2026)
Candidate pair No. 01, Anies Baswedan, is supported by the National Awakening Party (PKB), the Prosperous Justice Party (PKS), and the Nasdem Party. He served as the Governor of DKI Jakarta (2017-2022) and as the Minister of Education and Culture in the Working Cabinet (2014-2016). His running mate, Muhaimin Iskandar, also known as Gus Imin, serves as the Chairman of the National Awakening Party (2019-2024) and was the Minister of Manpower and Transmigration in the United Indonesia Cabinet II (2009-2014). The heated identity politics issue surrounding candidate pair No. 01, Anies Baswedan and Cak Imin, originated from Anies Baswedan attending the ulama ijtima, sparking accusations that the AMIN pair is using identity politics to secure the majority vote and win the 2024 presidential election. The mass media serves as a means of communication and information dissemination, capable of spreading and absorbing information on a large scale, thereby influencing social change. The power of the mass media to shape public opinion is then utilized by certain groups. This study aims to examine how the representation of the identity politics issue surrounding Anies–Cak Imin in the 2024 presidential election is portrayed in the news coverage of Kumparan.com and MetroTV, known for their professionalism and ideological stances, using Robert N. Entman's framing analysis. This model is built on the assumption of how media discussions reflect or select the appropriate perspective to tell a news story (news frame). Keywords: Anies-Cak Imin's, Framing Analysis, Identity Political Issue, Kumparan.com, Representation, , Metro TV ABSTRAKPasangan calon Nomor urut 01 Anies Baswedan yang diusung dari Partai Kebangkitan Bangsa (PKB), Partai Keadilan Sejahtera (PKS) dan Partai Nasdem yang menjabat sebagai Gubernur DKI Jakarta (2017-2022), Menteri Kebudayaan Pendidikan Dasar dan Menengah Kabinet Kerja (2014-2016) dan wakilnya Muhaimin Iskandar atau yang sering disapa dengan nama Gus Imin menjabat sebagai Ketua Umum Partai Kebangkitan Bangsa (2019-2024), Menteri Tenaga Kerja dan Transmigrasi Kabinet Indonesia Bersatu II (2009-2014). Isu politik identitas yang berlangsung panas dari pasangan calon nomor urut 01 yakni Anies Baswedan dan Cak imin berawal dari Anies Baswedan yang menghadiri ijtima ulama dan muncul isu-isu Pasangan AMIN menggunakan politik identitas untuk mengambil suara terbanyak dan menang di Pilpres 2024. Media massa merupakan sarana komunikasi dan informasi yang dapat menyebar dan menyerap informasi dalam jumlah besar sehingga dapat memengaruhi perubahan sosial. Kekuatan yang dimiliki media massa untuk membentuk opini publik ini kemudian digunakan oleh beberapa kalangan. Kata Kunci: Analisis Framing, Representasi, Anies-Cak Imin, Kumparan.co, MetroT, Pemberitaan, Politik Identitas